The left side of motor resonance - Sartori, Luisa; Begliomini, Chiara; Panozzo, Giulia; Garolla, Alice; Castiello, Umberto (Frontiers in Human Neuroscience, 2014)
Motor resonance is defined as the internal activation of an observer’s motor system, specifically attuned to the perceived movement. In social contexts, however, different patterns of observed and executed muscular activation are frequently required. This is the case, for instance, of seeing a key offered with a precision grip and received by opening the hand. Novel evidence suggests that compatibility effects in motor resonance can be altered by social response preparation. What is not known is how handedness modulates this effect. The present study aimed at determining how a left- and a right-handed actor grasping an object and then asking for a complementary response influences corticospinal activation in left- and right-handers instructed to observe the scene. Transcranial magnetic stimulation (TMS)-induced motor evoked potentials (MEPs) were thus recorded from the dominant hands of left- and right-handers. Interestingly, requests posed by the right-handed actor induced a motor activation in the participants’ respective dominant hands, suggesting that left-handers tend to mirror right-handers with their most efficient hand. Whereas requests posed by the left-handed actor activated the anatomically corresponding muscles (i.e., left hand) in all the participants, right-handers included. Motor resonance effects classically reported in the literature were confirmed when observing simple grasping actions performed by the right-handed actor. These findings indicate that handedness influences both congruent motor resonance and complementary motor preparation to observed actions.